2018
DOI: 10.3889/oamjms.2018.106
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Place for Local Natural Treatment of Psoriasis?

Abstract: BACKGROUND:Apitherapy is the medical use of honey bee products (honey, propolis, royal jelly, bee wax, and bee venom) to relieve human ailments, propolis in particularly, rich in essential oils such as flavonoid. Propolis is derived from tree buds and plants. It is considered as one of the most well-documented products from the honeybee and has always played an important role in traditional folk medicine. Another renowned plant is Aloe vera appertaining to the Liliaceae family. Its mucilaginous gel has been ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 10 publications
0
28
0
Order By: Relevance
“…This compound has been widely used in clinical trials, with promising antipsoriatic effects. A preclinical study on a mouse tail model of psoriasis used an ethanolic extract of Aloe vera gel which had significant positive effects on psoriatic skin (differentiation with orthokeratosis), comparable to those of tazarotene applications (42)(43)(44).…”
Section: Resultsmentioning
confidence: 99%
“…This compound has been widely used in clinical trials, with promising antipsoriatic effects. A preclinical study on a mouse tail model of psoriasis used an ethanolic extract of Aloe vera gel which had significant positive effects on psoriatic skin (differentiation with orthokeratosis), comparable to those of tazarotene applications (42)(43)(44).…”
Section: Resultsmentioning
confidence: 99%
“…This study showed that the PASI score decreased significantly in both groups; however, the reduction in the PASI score was greater in patients who received simvastatin [23], which agrees with our results. Also, a study reported by Wolkenstein et al disclosed that there was a decreased risk of psoriasis associated with the use of oral statins [24], [25], [26], [27].…”
Section: Discussionmentioning
confidence: 99%
“…Based upon our and published experiences, MTX is effective and affordable in psoriatic arthritis, affecting both skin lesions and joint damage. The price is more affordable than many biologic agents [6], [7], [8], [9], [10], [11], [12].…”
Section: Discussionmentioning
confidence: 99%